NILAI PENDIDIKAN DALAM NOVEL RANTAU 1 MUARA KARYA A. FUADI - Ade Ismail (Universitas Khairun, 2021)
This study aims to gain an understanding of the value of education in the novel Rantau 1 Muara by A.Fuadi. The focus of this research is on the value of religious education, moral education, social education and cultural education. The method used is descriptive qualitative method. The data in this study are text excerpts containing religious, moral, social and cultural educational values. The data were analyzed using the Miles and Huberman model, starting with data reduction, data modeling and drawing conclusions/verification. The results showed that there are four educational values in the novel Rantau 1 Muara by A. Fuadi, namely religious education, moral education values, social education values and cultural education values. The value of religious education emphasizes the balance between effort and prayer. The value of moral education is related to courage and honesty. Meanwhile, the value of social education emphasizes mutual care and togetherness. In addition, the value of cultural education lies in the importance of reading and writing culture.